(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to examine the effect of organizational commitment on improving the quality of banking services provided by Al-Mutahid Al-Ajilat Bank from the employees’ perspective. The study adopted the descriptive analytical approach. Primary data were collected through a questionnaire distributed to all employees of the bank, and (21) valid questionnaires were analyzed using SPSS software. The results revealed a high level of organizational commitment among employees and a high level of banking service quality. Statistical analysis also showed a positive and statistically significant effect of organizational commitment on improving banking service quality. This highlights the importance of enhancing organizational commitment as a key approach to improving service performance and strengthening the bank’s competitive position.